Areca nut alkaloids induce irreparable DNA damage and senescence in fibroblasts and may create a favourable environment for tumour progression. (28th September 2015) - Rehman, Ambreen; Ali, Sitara; Lone, Mohid Abrar; Atif, Muhammad; Hassona, Yazan; Prime, Stephen Stewart; Pitiyage, Gayani Nadika; James, Emma Louise Naomi; Parkinson, Eric Kenneth
Abstract : Background: Oral submucous fibrosis (OSMF) is a pre‐malignant condition that is strongly associated with the areca nut alkaloids, arecoline (ARC) and arecaidine (ARD). The condition is characterised by the presence of senescent fibroblasts in the subepithelial mesenchyme which have the potential to promote malignancy in the neighbouring epithelial cells. We tested the hypothesis that areca nut alkaloids induce senescence in oral fibroblasts and promote the secretion of invasion‐promoting transforming growth factor β (TGF‐β) and matrix metalloproteinase‐2 (MMP‐2). Methods: Two oral fibroblast lines were treated for 48h with ARC and ARD. Senescence‐associated β‐galactosidase (SA‐βGal) activity, Ki67 (cycling cells), large 53BP1 foci (irreparable DNA strand breaks) and p16 INK 4A (late senescence) were used as markers of cellular senescence and were quantified using indirect immunofluorescence and the ImageJ program. TGF‐β and MMP‐2 levels were measured using ELISA. Statistical analyses were performed with the two‐tailed unpaired t ‐test where n = 3 and the Wilcoxon–Mann–Whitney test where n = 6. Results: ARC (100 and 300 μM) and ARD (30 and 100 μM) significantly ( P < 0.05) induced fibroblast senescence, as determined by the increased expression of SA‐βGal, 53BP1 staining and CDKN2A /p16 INK 4A ; there was also a non‐significant reduction in Ki67 staining. Treated cells also showed a three‐ fivefold increase in TGF‐β and a small non‐significant increase in MMP‐2. Conclusions: Areca nut alkaloids induce senescence in oral fibroblasts and promote increased secretion of TGF‐β and perhaps MMP‐2 that may create a tissue environment thought to be critical in the progression of OSMF to malignancy.